Nigerian National Population and Housing Census, 2018 and Sustainable Development: The Issues at Stake - Mohammed, Isah Shehu; Othman, Muhammad Fuad; Osman, Nazariah (Journal of Techno-Social, 2019)
Conducting decennial population and housing census has, especially in developing states, remained the main source of quality demographic data. In Nigeria, National Population and Housing Censuses conducted in her history have not only been significant, but also problematic, sensitive, expensive, controversial exercises, yet very crucial source of statistical data for socio-economic, political and sustainable development. However, sustainable development cannot be achieved with mere census figures unless they are reliable for planning and implementation, as no matter how abundant human and material resources may be available and committed to such, sustainable development will only be a mirage without reliable statistics and plans. The earlier scheduled 2016 Population and Housing Census has been shifted to the year 2018 and this article explored the stake issues before the 2018 census exercise. There are for the 2018 census exercise, major issues/challenges of unity and cohesion of Nigerian state due to threats of renewed militancy in the Niger Delta; renewed agitations for re-structuring Nigerian state by the East and West parts of the country; issues of large nimber of refugees and internally displaced persons (IDP’s), especially within the North-East (Boko Haram) and North Central (Fulani/herdsmen-farmers conflict), and accessibility to many of those areas; feasibility of conducting it within the year (2018); proper and timely sourcing of funding, proper management/administration of ethno-religious issues of sensitive questions to be asked and answered and scams in recruitment/appointment of census officials and enumerators. The article recommended shift from the traditional and decennial to administrative census; intensive and extensive awareness and mobilization through (new social media, radio and other local and popular means of information dissemination) for the exercise; massive involvement of traditional and communities leaders; timely provision of logistics and transparent recruitment/appointment of adequate, but also competent personnel, and proper management of the data to be gathered during the exercise, openness in the conduct of the exercise to avoid unnecessary controversies and manipulation of figures for political, ethno-religious, regional and other negative interests.